Adaptive voltage control of gas tungsten arc welding. (19th June 2006) - Crawford, Reginald; Cook, George E.; Strauss, Alvin M.; Hartman, Daniel A.
An adaptive control based on fuzzy logic has been implemented for Gas Tungsten Arc Welding (GTAW). This adaptive controller eliminates the problems frequently experienced with traditional Automatic Voltage Control (AVC) systems, which do not adequately perform for all operational conditions because of the non-linear relationship between the arc voltage, current and arc length. This paper examines the differences between fuzzy logic control and adaptive fuzzy logic control of gas tungsten arc welding.